A source–grid–load coordinated power planning model considering the integration of wind power generation. (15th April 2016) - Zhang, Ning; Hu, Zhaoguang; Shen, Bo; Dang, Shuping; Zhang, Jian; Zhou, Yuhui
Highlights: We propose a novel source–grid–load coordinated power planning model. Generation expansion planning and transmission expansion planning are combined. Regulation capacities of power systems are considered in the planning model. The impacts of demand response are also taken into account in the planning. The approach to calculate wind power integration capacity is put forward. Abstract: Power system planning approach should meet the new requirements brought by continuous development of power systems. In recent years, wind power generation capacity keeps a rapid growth, but the problem of wind power curtailment becomes increasingly serious in some countries. The limitations of wind power integration produced by power systems, such as the inconsistency between installed generation capacity and transmission capacity and the insufficiency of regulation capacity, are drawing the attention in both academia and industry. This paper proposes a source–grid–load coordinated planning model for power systems with regulation capacity constraints being taken into account. In this novel model, traditional generation expansion planning and transmission expansion planning are integrated, and the peak-load regulation capacity and flexible regulation capability of power systems are considered. Meanwhile, the positive impacts of demand response are also taken into consideration. The numerical study verifies that the source–grid–load coordinated planning model can not only reduce the overall cost of the system, but also improve the wind power integration capacity and guarantee the sustainable development of wind power generation.